Air Quality Assessment by Moss Biomonitoring and Trace Metals Atmospheric Deposition - Pranvera Lazo; Alda Kika; Flora Qarri; Lirim Bekteshi; Shaniko Allajbeu; Trajce Stafilov (Aerosol and Air Quality Research)
Abstract Carpet-forming moss species are useful tools for monitoring the atmospheric deposition of pollutants like metals, organic compounds, nitrogen, and more recently, microplastics. Even with a dense sampling scheme, moss biomonitoring could extend the environmental study to national and/or continental scales. Moss species (Hypnum cupressiforme) was used as a biomonitor to assess the atmospheric deposition of metals in the entire territory of Albania and to identify the probable anthropogenic factors affecting the levels of the most toxic metals/metalloids (As, Cd, Co, Cr, Cu, Fe, Hg, Ni, Pb, and Zn) in the current moss. Statistical analysis is used to examine the relationships between elements accumulated in moss samples, and to assess the air quality of Albania. Considering the geochemical normalized data using lithium as a normalizing element, Fe, Cr, Co, and Ni show obvious anthropogenic anomalies. GIS maps identified the local enrichment of these elements, which is stretched in the north-southeastern direction and affected mostly by anthropogenic sources. The elements Fe, Cd, Cu, Pb, and Zn look likely to be homogenously distributed by indicating a common natural origin on a national scale. It is confirmed by the association of these elements with iron which is a typical crustal element that originates mostly from lithogenic dust in sparsely vegetation regions. Fe, Cd, Cu, Pb, and Zn were mostly higher between a few regions with few obvious anomalies positioned in the center of the country with high industrial activity, in the areas with heavy traffic, and in the cross-borders of Albania with Monte Negro and Greece mostly emerging from the local contribution of anthropogenic activities, local lithology, and transboundary pollution sources. The elements Cd and Hg are linked mostly with the long-range transport of pollutants.